Menelaah Kehendak Allah Bagi Orang Percaya Berdasarkan Roma 12:2 - Hendrick Sine; Alon Mandimpu Nainggolan (Institut Agama Kristen Negeri Manado, 2021)
This study aims to describe God's will for believers based on Romans 12: 2 as a form of responsibility after receiving God's grace. Indeed, building a life that understands the will of God and makes it happen in everyday life is very important for believers. The research method used is an inductive Bible study approach and literal and historical interpretation of the Bible. This research concludes that believers are responsible for realizing God's will in all dimensions of life after receiving God's grace. Discerning God's will is an effort to identify the things of what is good, pleasing to God, and perfect. Doing God's will means living ethically-practically according to His Word by keeping oneself from being conformed to the world and having one's mind renewed.